Analysis Of The EU Anti-dumping Policy In Terms Of The Revealed Comparative Advantages - Issabekov, Nurlybek; Suchecki, Adam Mateusz (Comparative Economic Research. Central and Eastern Europe, 2017)
Anti-dumping policy is an important instrument of trade policy as far as protecting markets against dishonest practices of foreign suppliers is concerned and it is compliant with international regulations such as e.g. these set by the World Trade Organisation. Generally, dumping concerns exporting commodities at lower prices than a selling price of commodities (so-called normal value). Anti-dumping policy uses appropriate preventive means against dishonest practices in a situation when: - commodity was brought to customs territory of an importing country at dumping prices, - import inflicted damage (or threatens to do it) to importing country’s industry. The first principles of anti-dumping policy were formulated in 1964 at the United Nations Conference and Development UNCTAD. The agreement was signed by 194 countries, including Poland. A similar agreement was also signed by the European Union countries. One of the types of agreements is tariff agreements in which a tool used as a system of cataloguing commodities in international trade is so-called Combined Nomenclature (CN). The system is used in customs proceedings and for registration needs. Anti-dumping proceedings also use HS classification system formulated by the World Customs Organization. The aim of the paper is to determine the proportion of goods covered by anti-dumping proceedings in the value of import conducted by the European Union between 1995–2012. In the empirical research the eight-digit commodity codes CN8 were used as well as HS2 codes that allow grouping imported commodities covered by anti-dumping proceedings by their manufacturing divisions. In that way a determined classification of commodities was used to describe a comparative advantage. To conduct assessment the modified Ballasa index (Bi) and Grupp/Legler index were used. The result of conducted analysis is determination of groups of commodities that are crucial for export of a given country.